Effect of different alternative additives on nutritional value, in vitro digestibility, and carbohydrate fractionation of whole-plant sorghum silage (Research, Society and Development, 2023)
This study aimed to evaluate the impact of different additives on nutritional value, in vitro digestibility, and fractionation of carbohydrates of sorghum silage. The experimental design was completely randomized with four replications and seven treatments: 1) Control (C), whole-plant sorghum with no additives; 2) Microbial (M), whole-plant sorghum + microbial additive (0.2% of original matter); 3) Sugar (S), whole-plant sorghum + brown sugar (4.0% of original matter); 4) Microbial plus sugar additives (MS), whole-plant sorghum + microbial additive (0.2% of original matter) + brown sugar (4.0% of original matter); 5) Whey (W), whole-plant sorghum + whey (3% of original matter); 6) Microbial plus whey additives (MW), whole-plant sorghum + microbial additive (0.2% of original matter) + whey (3% of original matter); 7) Microbial plus sugar plus whey (MSW), whole-plant sorghum + microbial additive (0.2% of original matter) + brown sugar (4.0% of original matter) + whey (3% of original matter). The sorghum was cut 111 days after emergence, in the milky-floury stage, and ensiled in polyvinyl chloride silos, adapted with a Bunsen valve. After 35 days of storage, the silos were opened, and samples were collected for the respective analyzes. The additives only presented differences for dry matter, mineral matter, organic matter, crude protein, ether extract, neutral detergent fiber, acid detergent fiber, total carbohydrates, and A + B1 fraction of the carbohydrates. In the present study, microbial inoculants, brown sugar, whey, and their interactions were effective in improving the chemical profile as well as the soluble carbohydrate fraction of whole-plant sorghum silage.